Kontribusi Pariwisata Halal terhadap Peningkatan Kunjungan Wisatawan Muslim di Asia Tenggara - Iqbal Aditya Pranata (Lembaga Penelitian dan Pendidikan, 2025)
Halal tourism has become one of the fastest-growing segments in the global tourism industry, particularly in Southeast Asia, where a large Muslim population provides both a significant market and a cultural foundation for its development. This study aims to analyze the contribution of halal tourism to the growth of Muslim tourist arrivals in Southeast Asia. Using a qualitative descriptive approach supported by secondary data from international tourism reports, this research highlights the role of halal-certified accommodations, Muslim-friendly services, and government support in shaping the region’s competitiveness as a halal tourism hub. The findings indicate that countries such as Malaysia, Indonesia, and Thailand have significantly increased their Muslim tourist arrivals through strategic policies, cultural integration, and industry adaptation to halal principles. Furthermore, the study reveals that halal tourism not only benefits the Muslim tourist market but also contributes to sustainable tourism practices by emphasizing ethical consumption and inclusivity. This research concludes that the expansion of halal tourism in Southeast Asia is a key driver in strengthening the region’s tourism competitiveness while fostering cultural harmony and economic growth.